(untitled) (International journal of medical sciences, 2026)
The article examines a study examining the relationship between ultrasound signs of liver steatosis and clinical and biochemical indicators in patients with non-alcoholic fatty liver disease. Laboratory tests were also conducted to determine the levels of alanine aminotransferase, aspartate aminotransferase, and lipid spectrum indicators. The most common chronic pathologies of the hepatobiliary system and its relationship to metabolic disorders have been described. Early diagnosis of the disease is important for the prevention of progression and development of complications. Ultrasound is an accessible, non-invasive, and widely used method for detecting liver steatosis. The obtained results allow us to determine the diagnostic significance of ultrasound criteria in assessing the degree of liver damage and their relationship with clinical and biochemical indicators.